The importance of continuing research during the demolition of architectural wooden architecture on the example of pens from Kaniczek translocated into 'Olęder' Ethnographic Park in Nieszawka Wielka - Maślak, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
'Olęder' Ethnographic Park in Nieszawka Wielka is Poland's only open-air museum that has been dedicated to construction of the rural, associated with olęder settlement. Currently, its research range covers an area of Lower Vistula Valley. Existing conservation measures, which main task is to protect architectural monuments in situ, however, is not always sufficient or possible. Preserved until today, very few examples of this construction are threatened by the progressive deterioration leading to their elimination from the Vistula landscape. The creation of a museum in the open air and translocation of these precious relics is actually the only chance for their continued survival. As a preliminary point, I will briefly present the characteristics of the 'olęder' settlement in the Lower Vistula Valley and the concept of 'Olęder' Ethnographic Park in Nieszawka Wielka along with attempts to establish a new branch of the Museum. The purpose of this article is to highlight the importance of supporting architectural research during the demolition of wooden architecture on the example of pens in Kaniczek translocated into 'Olęder' Ethnographic Park in Nieszawka Wielka. Initially, the concept of conservation project was discussed, developed on the basis of architectural research conducted before demolition. These studies were conducted using a non-invasive method, making it difficult to access all components and places. Supplementing the research during the demolition shed a new light on conservation issues. The summary of activities related to the translocation will show the last phase of facility construction.